A jornada da alma na dança dos caboclos: os símbolos de transformação na umbanda numa perspectiva interdisciplinar - Matalon, Carlos Elias (2014)
This thesis aims to identify the archetypes according to the psychology of Carl Gustav Jung, implicit in mythical motifs of Umbanda . Interest in this study arose from recent academic research that highlighted the importance of Umbanda religious practice to balance psychosocial and mental health practitioners. This guideline is part of the study the postulates of Carl Jung, bringing its theoretical framework longitudinally, for interdisciplinary dialogue with other disciplines relevant to the subject as: mythology, history, sociology and anthropology. It is used as a methodology to literature and literature of the works of Jung and some of his predecessors. The first chapter deals of the social and historical context of the origin of religion and these influences the institutionalization and symbolic construction of Umbanda. In the second follow- up addressing the themes of religion , mythology and designing individual in african - Brazilian worship seeking to glimpse the world of representation of Aboriginal and African of Umbanda religious universes present in their ethnic roots, is still made , a discussion of the myth of rebirth in the spiritual philosophy and psychology of archetypes . The study of Umbanda religious universe is the third chapter, aiming to situate the presence of Umbanda symbols in the liturgical and ritual context. One goes in the fourth chapter to approach the umbandista mediumship practice as identification with the present in mythical archetype. Assume the psychological aspects of religious practice, the psychological process of symbolic transformation, the experience of the numinous, as well as deepen the concept of archetype according to analytical theory. If we list to follow this last chapter, the ten mythical motifs present in religion and its archetypal psychological correspondences; finalize with some considerations about the possible influence of these archetypes in the expansion of consciousness level process, called the Jungian theory of individuation. The results of this study show the existence of the mythical motifs that can be addressed according to the psychology of archetypes in the symbols of Umbanda, indicating the possibility that the psychic experience of these aspects, when controlled and systematized, can promote mental balance and the expansion of consciousness.